Fitz-Hugh-Curtis Syndrome in a Male Patient: A Case Report and Literature Review - Shireesh Saurabh; Eric Unger; Constantinos Pavlides (Case Reports in Surgery)
Fitz-Hugh-Curtis syndrome is a condition characterized by inflammation of the liver capsule with concomitant pelvic inflammation without involvement of liver parenchyma. It is classically seen in young women who present with sharp, pleuritic right upper quadrant pain, usually but not always accompanied by symptoms of pelvic inflammatory disease (PID), and is frequently confused with biliary tract disease. Rarely the syndrome has been reported in males, and hematogenous and lymphatic spread to liver is thought to be the underlying mechanism. Serological tests and computed tomography (CT) scan may aid in diagnosis of Fitz-Hugh-Curtis syndrome. Definitive diagnosis is made by laparoscopy, which provides both diagnostic and therapeutic benefits. We report a case of Fitz-Hugh-Curtis syndrome in a young male patient, which was diagnosed and treated by laparoscopy. We also include a review of the literature.